Variasi Leksikal Bahasa Kerinci antar Desa Pulau Tengah, Desa Benik, dan Desa Jujun: Kajian Dialektologi - Restu Cahaya Salsabila; Ade Kusmana; Hilman Yusra; Andiopenta Purba (Universitas Islam Sumatera Utara, 2026)
This study examines the lexical variation of the Kerinci language across Pulau Tengah, Benik, and Jujun Villages in Keliling Danau District, Kerinci Regency, in response to linguistic diversity shaped by geographical and socio-cultural dynamics. The research addresses the question of how lexical differences manifest among these speech communities and to what extent such differences indicate dialectal variation. Employing a qualitative descriptive approach, the study utilizes 200 basic vocabulary items based on the Morris Swadesh list, with data collected through observation, interviews, elicitation, recording, and note-taking techniques. The data were analyzed through transcription, identification, classification, and dialectometric calculation. The findings reveal that 36 out of 200 glosses exhibit lexical variation, indicating differences in form while maintaining similar meanings across the three villages. Dialectometric analysis shows a difference percentage of 16%, which falls within the “no significant difference” category (0%–20%). These results suggest that despite observable lexical variation, the Kerinci language in the three locations remains relatively homogeneous, influenced by close geographical proximity, social interaction, and shared cultural practices.